Pengasuhan Positif Sebagai Upaya Ketahanan Keluarga Dalam Pencegahan Penyalahgunaan Narkoba - Nurul Aiyuda; Itto Nesyia Nasution; Rizal Effendi Putra; Rion Nofrianda (Universitas Negeri Padang, 2022)
This activity aims to increase parental knowledge through psychoeducation on the stages of adolescent development, positive parenting and self-awareness. This is done to provide understanding to parents related to adolescent parenting based on their stages of development and to build parenting potential through self-knowledge. This activity was carried out for 3 days in the village of Teratak Manuk, Pelalawan Regency, with 10 participants, parents of teenagers. The hope is that with the provision of psychoeducational materials regarding parenting, parents can better understand the stages of development of their children, who in this case are in their teens, and can be a preventive measure to build family resilience in overcoming drug abuse.